Time for laughter - BONIN, FRANCESCA; VOGEL, CARL (My University, 2014)
Social signals are integral to conversational interaction and constitute a large part of the social dynamics of multiparty communication. Moreover, social signals may also have a function in discourse structure. We focus on laughter, exploring the extent to which laughter can be shown to signal the structural unfolding of conversation and whether laughter may be used in the signaling of topic changes. Recent research supports this hypothesis. We investigate the relation between laughter and topic changes from two different points of view (temporal distribution and content distribution) as visible in the TableTalk corpus and also in the AMI corpus. Consistent results emerge from studies of these two corpora. Laughter is less likely very soon after a topic change than it is before a topic change. In both studies, we find solo laughter significantly more frequent in times of topic transition than in times of topic continuity. This contradicts previous research about the social dynamics of shared versus solo laughter considering solo laughs as signals of topic continuation. We conclude that laughter has quantifiable discourse functionality concomitant with social signaling capacity.
PUBLISHED
Keywords: AMI; Social signals; Laughter; Topic change; Discourse analysis; Conversational analysis; TableTalk; Ageing; Digital Humanities; Intelligent Content & Communications; Telecommunications; Computational linguistics; Discourse & Dialogue; Discourse analysis; conversation analysis; laughter; social signals; topic change